Inoculation with chlamydospores of Trichoderma asperellum SM-12F1 accelerated arsenic volatilization and influenced arsenic availability in soils - Xiu-rong WANG; Shi-ming SU; Xi-bai ZENG; Ling-yu BAI; Lian-fang LI; Ran DUAN; Ya-nan WANG; Cui-xia WU (Journal of Integrative Agriculture, 2015)
Fungi capable of arsenic (As) accumulation and volatilization are hoped to tackle As-contaminated environment in the future. However, little data is available regarding their performances in field soils. In this study, the chlamydospores of Trichoderma asperellum SM-12F1 capable of As resistance, accumulation, and volatilization were inoculated into As-contaminated Chen-zhou (CZ) and Shimen (SM) soils, and subsequently As volatilization and availability were assessed. The results indicated that T. asperellum SM-12F1 could reproduce well in As-contaminated soils. After cultivated for 42 days, the colony forming units (cfu) of T. asperellum SM-12F1 in CZ and SM soils reached 1010−1011 cfu g−1 fresh soil when inoculated at a rate of 5.0%. Inoculation with chlamydospores of T. asperellum SM-12F1 could significantly accelerate As volatilization from soils. The contents of volatilized As from CZ and SM soils after being inoculated with chlamydospores at a rate of 5.0% for 42 days were 2.0 and 0.6 μg kg−1, respectively, which were about 27.5 and 2.5 times higher than their corresponding controls of no inoculation (CZ, 0.1 μg kg−1; SM, 0.3 μg kg−1). Furthermore, the available As content in SM soils was decreased by 23.7%, and that in CZ soils increased by 3.3% compared with their corresponding controls. Further studies showed that soil pH values significantly decreased as a function of cultivation time or the inoculation level of chlamydospores. The pH values in CZ and SM soils after being inoculated with 5.0% of chlamydospores for 42 days were 6.04 and 6.02, respectively, which were lowered by 0.34 and 1.21 compared with their corresponding controls (CZ, 6.38; SM, 7.23). The changes in soil pH and As-binding fractions after inoculation might be responsible for the changes in As availability. These observations could shed light on the future remediation of As-contaminated soils using fungi.